Pengaruh Variasi Sudut Kemiringan Dan Debit Air Terhadap Daya Dan Efisiensi Turbin Air Vortex - Fadillah Abdul Ayiz; Danar Susilo Wijayanto; Yuyun Estriyanto (Nozel : Jurnal Pendididikan Teknik Mesin, 2022)
The vortex turbine is a moving turbine using artificial whirlpools that will then be converted into alternate energy turbines on the axis. The purpose of this study is to find out how high the Angle of skeleton tilt and dissipation of water affects the electricity and efficiency generated by vortex's water turbines. This study is using experimental methods. The study involves a few steps by preparing water turbines, sets up tools, data retrieval, and data analysis. The research free variable is a variant of the Angle of the skeletal tilt at 0, 5, 10 and a discharge of water at 6.34 l/s, 7.41 l/s, and 8.29 l/s. The bound variables of research are vortex's type of electric power and electricity efficiency. The research control variable is vortex turbine blade and vortex water turbine. The research instrument used is multimeter-based arduino, flowmeter-based arduino, tachometer, bow and digital balance. Data analysis techniques using quantitative descriptive analysis. The test conducted based on variations of water discharge at 6.34 l/s, 7.41 l/s, and 8.29 l/s and skeletal variant turbine gradient at 0, 5, and 10 of the power and efficiency of the turbines generated. Research shows that the maximum data of electrical calculation is obtained on water-discharge at 8.29 l/s with a tilted point 10 which was 10.3 watts, while the maximum efficiency data is obtained on water-diacharge at 8.29 l/s with a tilted point 10 which was 42.9%.